2018
DOI: 10.3390/s18082738
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Wrist Band-Type System for Multimodal Biometrics Integrated with Multispectral Skin Photomatrix and Electrocardiogram Sensors

Abstract: Multimodal biometrics are promising for providing a strong security level for personal authentication, yet the implementation of a multimodal biometric system for practical usage need to meet such criteria that multimodal biometric signals should be easy to acquire but not easily compromised. We developed a wearable wrist band integrated with multispectral skin photomatrix (MSP) and electrocardiogram (ECG) sensors to improve the issues of collectability, performance and circumvention of multimodal biometric au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our proposed schemes could provide secure ECG biometrics to the cases with limited access to others' ECG data or with limited computation power and memory. Examples are low-cost wearable bands with ECG sensors such as [18] or other recently commercialized wearable bands/sensors. We, along with other researchers, have showed that it is possible to achieve state-of-the-art authentication performance (0.1% EER) with multimodal biometrics using ECG and MSP (multispectral skin photomatrix) by storing all user information [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our proposed schemes could provide secure ECG biometrics to the cases with limited access to others' ECG data or with limited computation power and memory. Examples are low-cost wearable bands with ECG sensors such as [18] or other recently commercialized wearable bands/sensors. We, along with other researchers, have showed that it is possible to achieve state-of-the-art authentication performance (0.1% EER) with multimodal biometrics using ECG and MSP (multispectral skin photomatrix) by storing all user information [18].…”
Section: Discussionmentioning
confidence: 99%
“…Examples are low-cost wearable bands with ECG sensors such as [18] or other recently commercialized wearable bands/sensors. We, along with other researchers, have showed that it is possible to achieve state-of-the-art authentication performance (0.1% EER) with multimodal biometrics using ECG and MSP (multispectral skin photomatrix) by storing all user information [18]. Since our proposed methods yielded comparable performance to the baseline ECG biometrics, it seems possible for our proposed cancelable biometrics methods to achieve similar state-of-the-art authentication performance in a secure way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation